2019
DOI: 10.1007/s10103-019-02867-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy for weight reduction: a randomized pilot study

Abstract: Obesity and overweight is a global health crisis and novel methods of treatment are needed to address it. Low-level laser therapy (LLLT) is a currently available non-invasive procedure for lysing excess fat, but there is a lack of consensus exists on LLLT frequency and limited research from studies of LLLT. The purpose of this pilot study is to compare the effect of three of the most common LLLT frequencies on weight, waist circumference, body fat percentage, and quality of life. Sixty overweight (body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Furthermore, our group showed that 4 weeks of PBMT (780 nm, 0.4 J/point, applied on quadriceps, upper hindlimbs and center of abdomen) reduced epididymal and mesenteric adipocyte F I G U R E 3 (Continued) area. Interestingly, there are many evidences in human studies showing that PBMT is effective in reducing body fat [65][66][67][76][77][78][79][80]. Together, the present results and the available literature suggest that PBMT might be used to reduce adiposity.…”
Section: Adipocyte Hypertrophy and Inflammatory Infiltratesupporting
confidence: 62%
“…Furthermore, our group showed that 4 weeks of PBMT (780 nm, 0.4 J/point, applied on quadriceps, upper hindlimbs and center of abdomen) reduced epididymal and mesenteric adipocyte F I G U R E 3 (Continued) area. Interestingly, there are many evidences in human studies showing that PBMT is effective in reducing body fat [65][66][67][76][77][78][79][80]. Together, the present results and the available literature suggest that PBMT might be used to reduce adiposity.…”
Section: Adipocyte Hypertrophy and Inflammatory Infiltratesupporting
confidence: 62%
“…However, there is no comparison available regarding the best wavelength for this purpose. 18–22 28 Based on the localisation of fat tissue (more profound when compared with epidermis and dermis), this study will choose red and infrared light for the comparisons. The use of the same dosimetry, at these different wavelengths, will allow for the evaluation of the most suitable wavelength for body contouring.…”
Section: Discussionmentioning
confidence: 99%
“…This was in terms of improving the patients' quality of life and body satisfaction, as well as their weight, waist circumference, body mass index (BMI) and body fat mass reduction. 18 However, more studies are needed, in order to standardise the wavelength, the dosimetry and the application time, as well as the durability of the results achieved.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A research group reported a positive impact of PBMT on overweight individuals after six weeks of laser treatment when tested twice weekly. 26 In rats, PBMT was shown to cause a reduction in triglyceride levels, 27 suggesting a different mechanism of action than in the in vitro model that was generated in some, but not all, samples subject to triglyceride testing. However, some results regarding triglyceride levels were consistent with the results by Aquino et al 27 (Fig.…”
Section: Discussionmentioning
confidence: 99%